Thoracic processi spinosi findings agree among subjective, semiquantitative, and modified semiquantitative scintigraphic image evaluation methods and partially agree with clinical findings in horses with and without thoracolumbar pain. Issue 2 (5th November 2018) - van Zadelhoff, Claudia; Ehrle, Anna; Merle, Roswitha; Jahn, Werner; Lischer, Christoph
Abstract: Impinging processi spinosi in the equine thoracic spine are a common cause of poor performance in the horse. A modified semiquantitative scintigraphic image analysis has been proposed for the evaluation of equine processi spinosi . This technique showed a high inter‐ and intraobserver agreement when compared to subjective and semiquantitative image analysis. The aim of this retrospective, method comparison study was to evaluate the agreement of the modified semiquantitative scintigraphic image assessment with previous methods of interpretation and to compare these scintigraphic evaluation techniques with radiographic and clinical findings. Two hundred twenty‐three Warmblood horses that underwent scintigraphic, radiographic, and clinical examination of the thoracic spine were included in the study. Scintigraphic images were assessed using subjective, semiquantitative, and modified semiquantitative techniques. Radiographs were subjectively graded and horses were assigned to a group with or without thoracolumbar pain. Total radiographic and total scintigraphic grades were higher in horses with thoracolumbar pain ( P  < 0.05). Both the semiquantitative and the modified semiquantitative uptake ratios did not differ significantly in horses with or without thoracolumbar pain. The kappa agreement showed a substantial agreement between the modified semiquantitative scintigraphic and the semiquantitative scintigraphic evaluation techniques. The agreement between subjective scintigraphic and modified semiquantitative scintigraphic image evaluations was fair. There was a slight agreement between all scintigraphic techniques and radiographic findings. Limitations were the definition of thoracolumbar pain and the image analysis being restricted to the caudal thoracic processi spinosi . In conclusion, the modified semiquantitative scintigraphic image assessment obtained consistent results but did not perform better than previous evaluation methods. Further comparison to a defined diagnosis is warranted.